2005
DOI: 10.5511/plantbiotechnology.22.51
|View full text |Cite
|
Sign up to set email alerts
|

Independent roles of glutathione and O-acetyl-L-serine in regulation of sulfur-responsive gene expression in Arabidopsis thaliana

Abstract: We investigated the effects of a four-day treatment with 0.3 mM glutathione (GSH) and 10 mM O-acetyl-Lserine (OAS), negative and positive regulators of sulfur-responsive gene expression, respectively, alone or in combination, on the sulfur-responsive gene expression in ten-day-old Arabidopsis thaliana plants. We determined the relationship between the concentrations of GSH, OAS and sulfate, and expression of sulfur-responsive genes in rosette leaves. The concentrations of GSH and OAS correlated negatively and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Instead, it is more likely that this OAS accumulation was caused by perturbed GSH degradation, considering that the ggct2;1 mutant similarly showed higher OAS levels under sulfur deficiency. Although the expression levels of OAS-responsive genes such as APR3, SDI1, and GGCT2;1 (Aarabi et al, 2020;Watanabe et al, 2021) were not significantly affected by this OAS accumulation (Figure 5a), this can be well explained according to the report by Sogawa et al (2005). They reported that additional OAS application does not induce sulfur-responsive gene expression when plants are already exposed to sulfur deficiency, and also found that GSH negatively regulates sulfur-responsive gene expression.…”
Section: Discussionmentioning
confidence: 70%
“…Instead, it is more likely that this OAS accumulation was caused by perturbed GSH degradation, considering that the ggct2;1 mutant similarly showed higher OAS levels under sulfur deficiency. Although the expression levels of OAS-responsive genes such as APR3, SDI1, and GGCT2;1 (Aarabi et al, 2020;Watanabe et al, 2021) were not significantly affected by this OAS accumulation (Figure 5a), this can be well explained according to the report by Sogawa et al (2005). They reported that additional OAS application does not induce sulfur-responsive gene expression when plants are already exposed to sulfur deficiency, and also found that GSH negatively regulates sulfur-responsive gene expression.…”
Section: Discussionmentioning
confidence: 70%
“…A close relationship between amino acid transporters and GSP content has been reported in wheat and barley [23,33]. Clearly, the increased amino acid content in the innermost endosperm region might function in other regulatory mechanisms related to storage protein deposition, because it has been shown that amino acid precursors, such as O-aceylserine, regulate the GSP content [29,34].…”
Section: Discussionmentioning
confidence: 76%
“…O –acetylserine) or small peptides (e.g. GSH) also serve as signals in the regulation of grain N and S allocation to GSP (Sogawa et al ., ; Ohkama‐Ohtsu et al ., ). We observed coordinated changes between N, S and C metabolisms and GSP accumulation.…”
Section: Discussionmentioning
confidence: 99%